Interventional radiology procedures in biopsy and drainage - Gervais, Debra; Sabharwal, Tarun (Techniques in interventional radiology., 2011)
The Techniques in Interventional Radiology series of handbooks describes in detail the various interventional radiology procedures and therapies that are in current practice. The series comprises four titles, which in turn cover procedures in angioplasty and stenting, transcatheter embolization and therapy, biopsy and drainage and ablation. Forthcoming are volumes on pediatric interventional radiology and neurointerventional radiology. Each book is laid out in bullet point format, so that the desired information can be located quickly and easily. Interventional radiologists at all stages, from trainees through to specialists, will find this book a valuable asset for their practice. Interventional Radiology Procedures in Biopsy and Drainage presents the full array of operations using these techniques. The book is split into two sections ? one dedicated to biopsy procedures and the other to drainage procedures. Dr. Debra Gervais is Director of Pediatric Imaging and Associate Director of Abdominal Imaging and Intervention at Massachusetts General Hospital, Boston, Massachusetts, USA. Dr. Tarun Sabharwal is a Consultant Interventional Radiologist at Guy?s and St Thomas? Hospital, London, UK.